Growth and impact of asset securitization with respect to Singapore banks. - Kim, Neng Sin. (2010)
Asset Securitization, a new financial instrument which banks cannot ignore, is impacting the regional financial industry in ways unimaginable in the past. With the advent of Asset Securitization, regional banks suddenly find that they have a powerful tool to improve their financial position, reduce gearing, obtain cheaper funding and achieve higher liquidity all at the same time. However, the product life will be short lived if banks do not address some fundamental concerns regarding its economic value and perceived risk involved. Is Asset Securitization merely a device used by unscrupulous bankers to transfer value away from their creditors? Does it actually add value to the economy? This research focuses on two main concerns of Asset Securitization. In the first part, the paper investigates US banks to determine if there were any evidence of these banks diverting value away from their unsecured investors. This could be done through the sale of assets, e.g. asset securitization, therefore depleting the amount of collateral available to the creditors. From a study of 380 US banks over a six-year period there was no evidence to support this hypothesis. The second part focuses on the growth of Asset Securitization with respect to the local banks. The research emphasis is on growth, motivation, risk, and other issues related to asset securitization from the banks' perspective. Since asset securitization is relatively new in Singapore, there is no prior research available for reference, therefore an opinion survey of Singapore bankers had to be conducted to gauge the industry's perception towards these issues.